ANALISIS KARAKTERISTIK PARKIR DI DAERAH RUMAH SAKIT BHAYANGKARA MATARAM: Analysis Of Parking Characteristics In The Area Of Bhayangkara Hospital, Mataram - Safarudin, Safarudin; Dharma S., Bagus Widhi; Aminullah, Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
The purpose of this study was to determine the characteristics of motorcycle parking in the Bhayangkara Mataram Hospital parking area, to determine the level of adequacy of the use of parking spaces that have been provided in the Bhayangkara Mataram Hospital parking area. The research method used in this study was a survey conducted in the Bhayangkara Mataram Hospital parking area. The survey was conducted by placing surveyors at the gate in order to find out which vehicles were entering and leaving. The results of the study showed that the characteristics of parking at the Bhayangkara Mataram Hospital showed fluctuating parking volume and accumulation values ​​for each time period and day of data collection, but had a tendency for maximum values ​​during the hospital's operating hours when serving specialist doctor practices at the hospital. The level of adequacy of the parking area at the Bhayangkara Hospital is categorized as still being able to accommodate the number of visiting vehicles. This can be seen from the parking index which is still below the maximum parking standard.